Assessing the Value of Market Access from Belt and Road Projects - Reed, Tristan; Trubetskoy, Alexandr (World Bank, Washington, DC, 2019)
The present value of market access from the Belt and Road Initiative in Eurasia does not exceed its costs. Many transportation projects are of little value because they fail to create new least-cost paths between large population centers, or because they create redundancy with paths already on the network. If built in isolation, only about one-third of projects provide market access gains. However, considering the proposed new transport infrastructure as a system, the share of projects that provide gains increases to almost two-thirds. International coordination and rigorous project selection allow mutual benefit from the investment program.